Screening of Superabsorbent Polymers in Barley Husk - Yadav, Ram Jeewan; Shrestha, Ganga (Prithvi Journal of Research and Innovation, 2019)
Superabsorbent Polymers (SAPs) as hydrogels are super-soaker organic materials - Carboxymethyl Cellulose (CMC) which swells in water to form a clear gel. These are different from conventional absorbent sponge in which water can be wrung out easily; the SAPs' hydrate gel particle retains the absorbed water even under pressure. This unique ability to hold absorbed water, even against pressure, is the primary benefit of using SAPs. Such SAPs have created a very attractive area in the viewpoint of super-swelling behaviour, chemistry, and designing the variety of final applications. Besides various applications, the most volume of SAPs world production (106 tons/year) is yet consumed in hygienic uses, i.e., disposable diapers (as baby or adult diapers, feminine napkins, etc.). Agro wastes like Barley husk can be a very potential resource to obtain CMC or SAPs. This paper discusses extraction of α-cellulose followed by carboxy-methylation process to get CMC from barley husk. Absorbency tests of the CMC were performed by tea bag method and all the samples were characterized by FTIR.